2021
DOI: 10.3390/coatings11121495
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Research on Piezoelectric Performance of Electrospun PVDF Fiber Membranes with Inorganic Reinforced Materials

Abstract: The electrospun PVDF fiber membranes with the characteristics of light weight, strong signal and measurability, have been widely applied in the fields of environment, energy sensors and biomedical treatment. Due to the weakness of the piezoelectric and service properties, the conventional PVDF fiber membranes cannot meet the operating requirements. Based on the obtained optimal technological parameter of electrospun pure PVDF fiber membranes (P-PVDF) in the previous experiment (unpublished), three inorganic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…[78][79][80] It was found that the piezoelectric qualities of PVDF ber lms could be substantially boosted by doping silver nitrate (AgNO 3 ). 81 Under a shaker power unit with a frequency of 500 Hz and an amplitude of 5 mm, the output voltage was increased from 0.27 V to 2 V by adding 0.3 wt% AgNO 3 . Adding BiCl 3 to PVDF nanober composite lms could also enhance their b-phase content.…”
Section: Doping Modification Of Pvdf Nanofiber Filmsmentioning
confidence: 99%
“…[78][79][80] It was found that the piezoelectric qualities of PVDF ber lms could be substantially boosted by doping silver nitrate (AgNO 3 ). 81 Under a shaker power unit with a frequency of 500 Hz and an amplitude of 5 mm, the output voltage was increased from 0.27 V to 2 V by adding 0.3 wt% AgNO 3 . Adding BiCl 3 to PVDF nanober composite lms could also enhance their b-phase content.…”
Section: Doping Modification Of Pvdf Nanofiber Filmsmentioning
confidence: 99%
“…In another work, multiple functional materials can be used to achieve the synergistic effect on performance improvement. By using three kinds of inorganic doping materials of AgNO 3 , FeCl 3 •6H 2 O and nano graphene to modify the electrospun PVDF nanofiber mat, Li et al [109] prepared a composite piezoelectric nanofiber material (Figure 9b) and the voltage peak reached 1.8 V. It was tested that the dopant could effectively promote the formation of 𝛽 phase, thereby improving the piezoelectric properties. In addition, the static bending strength and elastic modulus were also enhanced.…”
Section: Piezoelectric Nanofiber-based Sensorsmentioning
confidence: 99%
“…b) A composite piezoelectric nanofiber material. Adapted with permission [109]. Copyright 2021, Coatings.…”
mentioning
confidence: 99%
“…Because the addition of conductive particles increases the surface charge density of the jet during electrospinning, the bending whipping effect of the jet is enhanced, the fiber is better stretched, and the content of β phase is relatively improved. Li et al [ 111 ] studied the piezoelectric properties of electrospun composite NFs with the addition of AgNO 3 , FeCl 3 ·6H 2 O, and modified graphene to PVDF. The relevant data are shown in Table 2 .…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 111 ], copyright 2021, MDPI. ( 4 ) the piezoelectric signals of the fiber membrane when different amounts of modified nanographene were added.…”
Section: Figurementioning
confidence: 99%